2021
DOI: 10.26656/fr.2017.5(s1).037
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of banana peel powder in functional food products

Abstract: Saba banana is one of the most favourite banana varieties in Malaysia. It also generates a concerning amount of waste as the only value part is the pulp. Banana peel has been proven to have a lot of nutritional content that should not be ignored and wasted. Conversion of banana peel to powder will convert it into a value-added product in the food industry. Preliminary study on the protein, moisture, crude fibre and fat was carried out for 2 different stages of maturity which are stage 2 (light green) and stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This implies that low pH favours the electrostatic forces which regulate rate of the adsorption of heavy metal on adsorbent sites. In the same vein, the decrease observed after pH 2 and 4 is due to lowering of the attraction between the positively charged lead metal ions and the negatively charged adsorbent (Negara et al, 2019;Na et al, 2020;Mohd Dom et al, 2021). The result obtained tallies with those reported by Khairiah et al (2021) in which optimum pH is 2.…”
Section: Effect Of Contact Time On Adsorption Of Zn Ionssupporting
confidence: 73%
“…This implies that low pH favours the electrostatic forces which regulate rate of the adsorption of heavy metal on adsorbent sites. In the same vein, the decrease observed after pH 2 and 4 is due to lowering of the attraction between the positively charged lead metal ions and the negatively charged adsorbent (Negara et al, 2019;Na et al, 2020;Mohd Dom et al, 2021). The result obtained tallies with those reported by Khairiah et al (2021) in which optimum pH is 2.…”
Section: Effect Of Contact Time On Adsorption Of Zn Ionssupporting
confidence: 73%
“…Gelling properties of pectin are determined by their degree of esterification and lies in the range of 60 to 90% (21) In previous studies, it was reported that the degree of esterification is affected by temperature (22) . Depending on the degree of proportion, pectin can be divided into two parts-rapid settings (DE> 72%), slow setting (DE,58-65%) (23)…”
Section: Degree Of Esterificationmentioning
confidence: 99%
“…bp 2% had the greatest effect in reducing of Ks. This result could due to the higher water holding capacity of banana peel (Mohd Dom et al, 2021) that decrease movement of water so, the saturated hydraulic conductivity decreased compared with other amendments. Increase the application rate in all amendments significantly decreased the saturated hydraulic conductivity.…”
Section: Effect Of Soil Amendments On Saturated Hydraulic Conductivit...mentioning
confidence: 96%